Aspek Klinis dan Tatalaksana Duchenne Muscular Dystrophy Pada Anak - Tita Menawati Liansyah; Hidayaturrahmi Hidayaturrahmi (Jurnal Sinaps, 2022)
Duchenne muscular dystrophy (DMD) is an X-linked recessive disease, progressive muscular type, hereditary in nature, and is inherited through X-linked recessive so that it only affects boys, while girls are carriers. Usually patients die in the second decade due to complications of pulmonary infection or heart failure. Clinically DMD patients are unable to walk at the age of about 10 years. Surgery and rehabilitation, can help patients to prolong ambulation function and provide a sense of comfort.